Association of Serum Vitamin D Level and Serum Lipids Profile - Roxana Sadeghi; Mohammad Reza Eidi; Nasim Zamani (International Journal of Cardiovascular Practice, 2018)
Introduction: High level of vitamin D is associated with a better health status. The role of vitamin D deficiency in the incidence of cardiovascular events is demonstrated in previous studies. The current study aimed at evaluating the eﬀect of vitamin D supplement therapy on serum lipids profile, as a risk factor for cardiovascular diseases.Methods: The current prospective cohort study included 221 patients admitted to a university hospital from March 2014 to March 2015. The baseline levels of the patients' serum vitamin D and lipid profile of the study subjects were recorded. After three months treatment with vitamin D, the patients' serum vitamin D level and lipid profile were re-evaluated. The results before and after the supplement therapy were compared using statistical methods.Results: The mean age of the patients was 48.2 ± 14.0 years. The mean vitamin D level was 21.0 ± 16.6 ng/mL at baseline, which increased to 35.8 ± 32.7 ng/mL (P = 0.001) after a three-month vitamin D supplement therapy. Mean low-density lipoprotein (LDL) decreased from 112.1 ± 30.0 to 98.7 ± 31.7 mg/dL (P = 0.003) after the supplement therapy. Mean high-density lipoprotein (HDL) increased from 42.8 ± 11.2 to 44.5 ± 9.0 mg/dL, but the diﬀerence was insignificant before and after the treatment (P = 0.2). Mean cholesterol reduced from 183.8 ± 42.3 to 169.5 ± 41.9 mg/dL (P = 0.02) and the mean TG dropped from 147.5 ± 98.7 to 134.7 ± 71.1 mg/dL, (P = 0.1) after vitamin D intake.Conclusions: The mean levels of LDL and cholesterol significantly decreased during the three-month intervention; in addition, although some changes were observed in the level of HDL and TG, the diﬀerences were statistically insignificant. Further studies on larger sample sizes and longer follow-ups are recommended.